2010
DOI: 10.1117/12.852265
|View full text |Cite
|
Sign up to set email alerts
|

Nanoprobe maskless lithography

Abstract: Scanning probe-based methods for surface modification and lithography are an emerging method of producing sub 20-nm features for nanoelectronic applications. In this study, we have demonstrated the nanoscale lithography based on patterning of 10 to 50-nm-thick calix[4]arene by electric-field-induced electrostatic scanning probe lithography. The features size control is obtained using electrostatic interactions and depends on the applied bias and speed of the AFM tip. The width of the obtained lines and dots va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…In this manner, most of the difficulties for controlling the cantilever stiffness were overcome. 37,38 We investigated the force resolution of this cantilever in the frequency band of 0.1-1000 kHz and found that it is better than 75 pN. The cantilever sensors are routinely offering atomic step resolution at ambient room conditions.…”
Section: Compact Piezoresistive and Self-actuated Cantileversmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manner, most of the difficulties for controlling the cantilever stiffness were overcome. 37,38 We investigated the force resolution of this cantilever in the frequency band of 0.1-1000 kHz and found that it is better than 75 pN. The cantilever sensors are routinely offering atomic step resolution at ambient room conditions.…”
Section: Compact Piezoresistive and Self-actuated Cantileversmentioning
confidence: 99%
“…21,38 Recently, we have demonstrated the positive-tone, developmentless, so called "self-development" patterning of calixarene molecular glass resists using highly confined electric field, current-controlled scanning probe lithography (EF-CC-SPL) scheme. 6,7,38,39 Herein, an electric field is applied between scanning probe and sample, resulting in a current flux of low energy electrons (<50 eV), which is regulated by the lithography current feedback loop. This current flux in turn penetrates the molecular resist material below the nanoprobe, leading to a highly localized removal process used for patterning of nanofeatures.…”
Section: Scanning Probes In Nanostructure Fabricationmentioning
confidence: 99%
“…1,2,[16][17][18][19][20][21] Herein, a high nonuniform electric field, which causes a current of low energy electrons between the tip and sample, is applied for direct patterning of the calixarene resist. These low energy electrons (<50 eV), field emitted from the scanning probe tip apex (preliminary simulations provided in Ref.…”
mentioning
confidence: 99%
“…1,2 Scaling the feature sizes down to 10 nm and below allows us to use quantum-based effects such as quantized excitations, Coulomb blockade, and single-electron tunneling. 2 However, state-of-the-art manufacturing methods are far away from meeting the requirements to generate, overlay, and inspect features in a single digit nanoregime.…”
mentioning
confidence: 99%
“…In addition, sequential read-write cycle patterning combining positive and negative tone lithography is shown. We are presenting patterning over larger areas (80 x 80 µm) and feature the practical applicability of the lithographic processes.The ability to rapidly fabricate features in sub-10 nm regime in a reproducible manner has been identified as one of the most important task to enable novel nanoelectronic, NEMS, photonic and bio-nanotechnology based devices [1,2]. Scaling the feature size down to 10 nm and below allows us to use quantum based effects like quantized excitations, single-atom electron spin qubit in silicon, and Coulomb blockade and single-electron tunneling [2].…”
mentioning
confidence: 99%